The Compound of Ruptured Splenic Abscess and Severe Anemia: The Potential Life-Threatening Twins Requiring Specialized Care in Limited Resourced Rural Areas in Kilombero, Morogoro Tanzania - Tekie, Fassil; Karuhanga, Theresia Andrea; Gingo, Wilfred; Kaale, Sadikiel; Madoshi, Philbert (Medical Research and Its Applications Vol. 7, 2024)
The ruptured splenic abscess is usually uncommon but associated with significant life-threatening. Concurrence of ruptured splenic abscess and severe anemia may lead to death if not treated effectively, especially in limited health care. We present the 43-year-old who presented with generalized peritonitis due to a ruptured spleen. Also, she had severe anemia with hb of 4.3 g/dl. The cause of anemia was not immediately identified. However, tests for bacterial sensitivity revealed Klebsiella pneumoniae which was resistant to Ceftriaxone, Amoxiclav, Ceftizine and Cotrimoxazole but sensitive to Meropenem, Ciprofloxacin and Vancomycin. After the result, the treatment shifted to Meropenem1 Gm tds for 5/7. After seven days in the ward, the patient fully recovered and she was discharged in good condition.